2018
DOI: 10.3390/v10040201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rabies Virus by 1,2,3,4,6-Penta-O-galloyl-β-d-Glucose Involves mTOR-Dependent Autophagy

Abstract: The compound 1,2,3,4,6-penta-O-galloyl-β-d-glucose (PGG), a gallotannin present in various plants such as Rhus chinensis Mill and Paeonia suffruticosa, has a broad spectrum of antiviral effects. The present study investigated its potency against infection of mice with rabies virus (RABV). Results demonstrated that PGG strongly inhibited virus titers (50-fold), viral mRNA expression (up to 90%), and protein synthesis in vitro. Importantly, we found that PGG not only suppressed viral adsorption and entry, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Many viruses, including those of fish, activate/need autophagy to replicate 58,59,66,[78][79][80] . In this regard, there are some previous studies that have analysed the influence of autophagy on SVCV infection 54,57,58 ; however, the conclusions of these studies are contradictory with respect to the activation of autophagy as either a negative regulatory mechanism 54,57 or, as determined more recently, a mechanism required by the virus for replication 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses, including those of fish, activate/need autophagy to replicate 58,59,66,[78][79][80] . In this regard, there are some previous studies that have analysed the influence of autophagy on SVCV infection 54,57,58 ; however, the conclusions of these studies are contradictory with respect to the activation of autophagy as either a negative regulatory mechanism 54,57 or, as determined more recently, a mechanism required by the virus for replication 58 .…”
Section: Discussionmentioning
confidence: 99%
“…PGG took longer to reach the blood stream than other polyphenolic compounds and eventually existed in free form; plasma concentration of PGG was 3–4 μ M 2 hours post-injection. Similarly, PGG has been delivered in small animal models via IP routes for anxiolytic properties, 44 anti-viral treatment, 14,178 anti-tumor studies, 67,91 and anti-diabetic treatments. 186 Furthermore, PGG dosages up to 10 mg/kg have been used for the inhibition of capillary morphogenesis gene 2 in mice via the IP route.…”
Section: Current Issues With Pgg Administrationmentioning
confidence: 99%
“…Our previous study reported that PGG exhibits strong anti-RABV activity and multiple effects on the RABV life cycle (12). However, more studies were required to explore the underlying antiviral mechanisms of PGG, which would better promote its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Sample collection and mouse experiments were approved by the Administrative Committee on Animal Welfare of the Institute of Military Veterinary, China (Laboratory Animal Care and Use Committee Authorization, permit number JSY-DW-2016-02). Mice were randomly divided into 4 groups (n ϭ 51), with mouse infection and administration being conducted as described previously (12), Briefly, the mice were injected intramuscularly (i.m.) in both hind legs with a lethal dose of CVS-11 (10 50% lethal doses, 10 6.5 TCID 50 ) and 1 h later with intraperitoneal (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation